Penerapan Metode Icebreaker Dalam Pencapaian Tujuan Pembelajaran Latsar CPNS Oleh Fungsional Widyaiswara Pada Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Nusa Tenggara Barat - Gusti Lanang Rakayoga (Journal of Classroom Action Research, 2022)
The purpose of this study is to apply the Icebreaker method in achieving the learning objectives of the CPNS background. This research was conducted at the Regional Human Resources Development Agency of West Nusa Tenggara Province. The population of this study is all Widyaiswara BPSDMD of West Nusa Tenggara Province which amounts to 25 Widyaiswara people. Because the population is small, all the population of 25 Widyaiswara people is used as a research sample. The research method used in this study is a qualitative descriptive research method. Data collection techniques are carried out by collecting regulations from the State Administration Institution concerning Guidelines for the Implementation of Basic Training for Civil Servant Candidates which are integrated, especially related to the existence of the Regulation of the State Administration Institution of the Republic of Indonesia Number 25 of 2017, and Number 12 of 2018, Collection of Reading Books about Icebreaking, and questionnaires. Data analysis techniques are carried out through three steps, namely data processing; Data analysis; interpretation of the results of analysis, Data Processing. The results showed that the application of the Icebreaker method by the functional widyaiswara BPSDMD of West Nusa Tenggara Province in the basic training process of Civil Servant Candidates has supported